2021
DOI: 10.7150/thno.51265
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C activates pyruvate dehydrogenase (PDH) targeting the mitochondrial tricarboxylic acid (TCA) cycle in hypoxic KRAS mutant colon cancer

Abstract: Background: In hypoxic tumors, positive feedback between oncogenic KRAS and HIF-1α involves impressive metabolic changes correlating with drug resistance and poor prognosis in colorectal cancer. Up to date, designed KRAS-targeting molecules do not show clear benefits in patient overall survival (POS) so pharmacological modulation of aberrant tricarboxylic acid (TCA) cycle in hypoxic cancer has been proposed as a metabolic vulnerability of KRAS-driven tumors. Methods: Annexin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…One notable example of the progress in VitC pre-clinical research is the recent work in hard-to-treat Kirsten Rat Sarcoma Viral Oncogene Homolog (KRAS) driven tumours, such as KRAS mutant colorectal cancer (CRC) [ 25 , 27 , 32 ]. Based on prior studies by Yun et al [ 32 ] and Aguilera et al [ 25 ], Cenigaonandia-Campillo et al [ 27 ] used elevated doses of VitC (5–10 mM) in KRAS mutant CRC tumours, both in vitro and in vivo.…”
Section: High-dose Vitc As a Single Agentmentioning
confidence: 99%
See 2 more Smart Citations
“…One notable example of the progress in VitC pre-clinical research is the recent work in hard-to-treat Kirsten Rat Sarcoma Viral Oncogene Homolog (KRAS) driven tumours, such as KRAS mutant colorectal cancer (CRC) [ 25 , 27 , 32 ]. Based on prior studies by Yun et al [ 32 ] and Aguilera et al [ 25 ], Cenigaonandia-Campillo et al [ 27 ] used elevated doses of VitC (5–10 mM) in KRAS mutant CRC tumours, both in vitro and in vivo.…”
Section: High-dose Vitc As a Single Agentmentioning
confidence: 99%
“…One notable example of the progress in VitC pre-clinical research is the recent work in hard-to-treat Kirsten Rat Sarcoma Viral Oncogene Homolog (KRAS) driven tumours, such as KRAS mutant colorectal cancer (CRC) [ 25 , 27 , 32 ]. Based on prior studies by Yun et al [ 32 ] and Aguilera et al [ 25 ], Cenigaonandia-Campillo et al [ 27 ] used elevated doses of VitC (5–10 mM) in KRAS mutant CRC tumours, both in vitro and in vivo. They showed that VitC was able to target common metabolic aberrancies by decreasing adenosine triphosphate (ATP) and glucose transporter 1 (GLUT-1) levels, as well as by dissipating the mitochondrial membrane potential, which could sensitize KRAS mutant CRC cells to current treatments such as chemotherapy.…”
Section: High-dose Vitc As a Single Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that Vitamin C inhibits GAPDH and impairs cell growth specifically in KRAS and BRAF-mutant CRC cell line by interfering with glycolysis [150]. Aguilera et al reported that Vitamin C is also implicated in KRAS uncoupling from the plasma membrane, disrupting the expression of key metabolic enzymes and promoting cell death in KRAS-mutated cells [151]. Recently, the same group demonstrated that this compound, at pharmacological doses, can also modulate Krebs Cycle through PDK-1 (pyruvate dehydrogenase kinase 1) inhibition, again killing cells harbouring KRAS mutations but not those that are wild type [152].…”
Section: Targeting Ras-mediated Metabolic Reprogrammingmentioning
confidence: 99%
“…Targeting metabolism has emerged as a good strategy for managing KRAS-mutated CRC and, therefore, for overcoming anti-EGFR resistance. Indeed, it has been demonstrated in preclinical trials that Vitamin C is enough to sensitize KRAS-mutant cells to cetuximab in CRC [151] and Erlotinib in lung cancer [200], both in vivo and in vitro. Unfortunately, although Vitamin C is under clinical trials in combination with the anti-EGFR panitumumab in WT KRAS patients, no clinical trials targeting both metabolism and EGFR have been performed for KRAS-mutated CRC patients so far.…”
Section: Anti-ras Strategies: a New Ally For Improving Current Efgr-targeted Therapies?mentioning
confidence: 99%